Effects of Ultrasound on Follicular Atresia Count - Shadab Ahmed Butt , Shadab Ahmed Butt (Journal of Rawalpindi Medical College, 2009)
Background: To observe the morphological effects taking place in ultrasound treated rabbit’s ovaries by observing the total atretic follicles count. Methods: This experimental study was conducted at National Institute of Health Islamabad and Army Medical College Rawalpindi. Forty adult, non pregnant female rabbits (Oryctolagus Cuniculus strain) weight 900 gm-1500 gm were used. They were divided in four groups, I, II, III & IV, each containing ten rabbits, Group I was taken as control. Ovaries of others were exposed to ultrasound frequency of 3.5 MHz and intensity of 96 dB for two minutes for 3, 6 and 12 days. After euthanasia, ovaries were dissected, fixed and processed. Atretic follicles from the largest cross section stained by heamatoxylin and eosin were counted. Analysis of variance (ANOVA) was used for statistical comparison among groups. Results: The current study showed increase in total atretic follicles count especially in group III Conclusion: Exposure to ultrasound produces morphological changes in ovaries